2022
DOI: 10.3390/polym14153142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yam (Dioscorea rotundata) Mucilage on the Physical, Rheological and Stability Characteristics of Ice Cream

Abstract: In the present investigation, yam mucilage was evaluated as a stabilizer and emulsifier in the formulation of vanilla flavored ice cream; physicochemical, rheological, and stability characteristics were determined. A completely randomized bifactorial design was used (yam mucilage: Carboxymethylcellulose ratio with the following levels: 100:0, 80:20, 50:50, and 20:80, and stabilizers concentration with levels of 0.4 and 0.8%). Results showed an increase in the protein content present in ice cream mixture as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
2
1
0
1
Order By: Relevance
“…According to several studies, the pseudoplastic behavior of ice cream mixes have a flow index (n) below unity. The flow indices values both in Ostwald de Waele and Herschel-Bulkley models were 0.5286-0.5414 and 0.7459-0.7667, respectively, and remained in agreement with the literature data concerning various additives [58][59][60]. Surprisingly, in the samples with the addition of minerals at concentrations of 0.5% and 0.8%, a sudden and significant decrease in yield stress (σ 0 ) was observed (Table 4).…”
Section: Ice Cream Mixes Rheological Behaviorsupporting
confidence: 86%
“…According to several studies, the pseudoplastic behavior of ice cream mixes have a flow index (n) below unity. The flow indices values both in Ostwald de Waele and Herschel-Bulkley models were 0.5286-0.5414 and 0.7459-0.7667, respectively, and remained in agreement with the literature data concerning various additives [58][59][60]. Surprisingly, in the samples with the addition of minerals at concentrations of 0.5% and 0.8%, a sudden and significant decrease in yield stress (σ 0 ) was observed (Table 4).…”
Section: Ice Cream Mixes Rheological Behaviorsupporting
confidence: 86%
“…These high percentages of thixotropy may be due to the addition of some thickeners or stabilizers [25]. This behavior has been reported for dairy cream with some natural stabilizers [26,27], ice cream [28], and yogurt [29]. Furthermore, for the "sueros costeños" that present time dependence, the ascending curve is greater than the descending curve, so they show a positive thixotropy, where the viscosity decreases with time due to a change of the internal structure when a strain is applied.…”
Section: Rheological Behavior Of "Suero Costeño"supporting
confidence: 52%
“…Ultrasound facilitates the even distribution of all components in the ice cream mixture, including fat globules, while also providing the pasteurization effect. Previous studies have also shown that mucilage, such as chia seed mucilage [27,68], yam mucilage [69], and BSG [70], can be used as stabilizers in ice cream, resulting in similar characteristics to those obtained with commercial stabilizers (GG). Ice cream samples with mucilage exhibited higher degrees of aeration, longer melting times, and freezing point temperatures ranging from −6.1 to −2.8 • C.…”
Section: Physical Properties Of Ice Creammentioning
confidence: 91%